Psychological treatments for adults with posttraumatic stress disorder: A systematic review and meta-analysis - Cusack, Karen; Jonas, Daniel E.; Forneris, Catherine A.; Wines, Candi; Sonis, Jeffrey; Middleton, Jennifer Cook; Feltner, Cynthia; Brownley, Kimberly A.; Olmsted, Kristine Rae; Greenblatt, Amy; Weil, Amy; Gaynes, Bradley N. (Clinical psychology review, 2016)
Numerous guidelines have been developed over the past decade regarding treatments for Posttraumatic stress disorder (PTSD). However, given differences in guideline recommendations, some uncertainty exists regarding the selection of effective PTSD therapies. The current manuscript assessed the efficacy, comparative effectiveness, and adverse effects of psychological treatments for adults with PTSD. We searched MEDLINE, Cochrane Library, PILOTS, Embase, CINAHL, PsycINFO, and the Web of Science. Two reviewers independently selected trials. Two reviewers assessed risk of bias and graded strength of evidence (SOE). We included 64 trials; patients generally had severe PTSD. Evidence supports efficacy of exposure therapy (high SOE) including the manualized version Prolonged Exposure (PE); cognitive therapy (CT), cognitive processing therapy (CPT), cognitive behavioral therapy (CBT)-mixed therapies (moderate SOE); eye movement desensitization and reprocessing (EMDR) and narrative exposure therapy (low–moderate SOE). Effect sizes for reducing PTSD symptoms were large (e.g., Cohen's d ~−1.0 or more compared with controls). Numbers needed to treat (NNTs) were <4 to achieve loss of PTSD diagnosis for exposure therapy, CPT, CT, CBT-mixed, and EMDR. Several psychological treatments are effective for adults with PTSD. Head-to-head evidence was insufficient to determine these treatments' comparative effectiveness, and data regarding adverse events was absent from most studies. •We conducted a meta-analysis of psychological treatments for adults with PTSD.•We examined efficacy, comparative effectiveness, and harms.•Several therapies demonstrated efficacy, with strongest support for exposure.•Evidence was insufficient to determine comparative effectiveness.•Information on adverse events was generally not reported.